Effectiveness of Marine and Shipping Surveillance Through Patrol Reports at Class II Bitung Sea and Coast Guard Base - Damanik, Zoserijal; Sendouw, Recky; Pangkey, Itje (Technium Social Sciences Journal, 2025)
This study aims to analyze the reporting system of marine and shipping surveillance patrol results at the Class II Bitung Sea and Coast Guard Base, focusing on the structure and content of the report, the reporting mechanism, and the implementation of technology used in supporting the implementation of surveillance tasks. The method used in this research is a descriptive qualitative approach, with data collection through in-depth interviews to, direct observation of the patrol and reporting process, and documentation studies of the form and content of reports used. The results show that the reporting system implemented is still not standardized, with diverse and inconsistent report structures and contents. The reporting mechanism is still manual and does not support real-time reporting, while the utilization of digital technology such as reporting applications has not run optimally due to limited equipment, networks, and technical training for officers. As a result, the effectiveness of the report as a monitoring and decision-making tool is low, causing delays in operational follow-up in the field. This study recommends the need to develop national standards for patrol report formats and procedures, strengthen technological infrastructure on patrol vessels, continuous training for officers related to digital reporting systems, and develop a real-time-based integrated reporting system that supports cooperation across marine surveillance agencies. With these steps, the reporting system is expected to become an important element in strengthening the effective and sustainable monitoring and management of marine resources.